Can education institution implement STEM? From Malaysian teachers' view - Ramli, Nur Farhana; Talib, Othman (Human Resource Management Academic Research Society, 2017)
STEM (Science, Technology, Engineering, Mathematics) has been implemented in schools beginning 2017. The main objective of the paper is to find out the views of science teachers regarding the implementation of STEM in schools. This study utilized a qualitative approach in which interviews were carried out among five secondary school teachers who teach science subjects (science, biology, chemistry or physics). The results showed that teachers’ understanding in implementing STEM is insufficient. This was due to lack of information from the authorities. There are some barriers highlighted in this study which are motivation, syllabus, time constraints, lack of training, inadequate facilities, students’ involvement and school community response. This study suggests the urgent need for authorities to disseminate understanding and provide sufficient training to the teachers as well as to overcome the barriers as they are going to implement STEM in schools.